Social and vocational rehabilitation of people with disabilities - Dorota Tomczyszyn (Rozprawy Społeczne)
Abstract Rehabilitation of people with disabilities is a complex and multi-stage process. It starts with medical rehabilitation but an important part of it are social and vocational stages. There exist many barriers to the implementation of the rehabilitation process, incl. difficulties in accessing rehabilitation services, bureaucratization of the system, negative social attitudes towards people with disabilities, lack of jobs for those with disabilities or their low education. Thus, the importance of social and vocational rehabilitation is not limited to stimulating development. It is also related to the sense of meaning in life and the increase in self-esteem of people with disabilities. Accordingly, social and vocational rehabilitation of people with deficits has a direct impact on the process of their integration and inclusion in the social environment.